2021
DOI: 10.1364/oe.431006
|View full text |Cite
|
Sign up to set email alerts
|

Point spread function for the wide-field-of-view plenoptic cameras

Abstract: Recently, single or multi-layer spherical lens (monocentric lens) coupled with a microlens array (MLA) and an imaging sensor are under investigation to expand the field of view (FOV) for handheld plenoptic cameras. However, there lacks modeling the point spread functions (PSFs) for them to improve the imaging quality and to reconstruct the light field in the object space. In this paper, a generic image formation model is proposed for wide-FOV plenoptic cameras that use a monocentric lens and an MLA. By analyzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The concept of monocentric panoramic light field is proposed by combining a monocentric lens and light field sensors in [142]. The latest research showed that the system using the combination of monocentric lens and microlens array can significantly improve the imaging quality and light field reconstruction using the calculated point spread function model [143].…”
Section: E Monocentric Panoramic Systemmentioning
confidence: 99%
“…The concept of monocentric panoramic light field is proposed by combining a monocentric lens and light field sensors in [142]. The latest research showed that the system using the combination of monocentric lens and microlens array can significantly improve the imaging quality and light field reconstruction using the calculated point spread function model [143].…”
Section: E Monocentric Panoramic Systemmentioning
confidence: 99%